Membandingkan Demokrasi dan Penganggaran Partisipatif ala Porto Alegre-Brasil dan Musrenbang Partisipatif ala Indonesia - Kristianto Ratu Marius Naben (Yayasan Literasi Sains Indonesia, 2023)
This article is a literature study to make a comparison between the practice of participatory democracy and participatory budgeting from Porto Alegre and development planning deliberations practiced in Indonesia. The aim of this comparative study is to look further at community participation in planning, monitoring and evaluating public policy. Porto Alegre is one of the states in Brazil that has succeeded in developing participatory democracy to maximize public participation in state life. Participatory democracy is a form of collective decision-making process that combines elements of direct democracy from civil society and representatives or legislatures. The concrete manifestation of participatory democracy is participatory budgeting. In democracy and participatory budgeting, there is an open space for civil society to participate, dialogue and collaborate with the government, legislative members and other parties to design, implement and evaluate public policy. Community participation in planning programs and public policies is also practiced in Indonesia through development planning meetings. This deliberation is carried out from the village/sub-district level to the national level. However, the reality shows that the level of community participation in development planning meetings is still low for various reasons. This study concludes that the democratic and participatory budgeting model is more successful in mobilizing community participation than the development planning meetings.